EXCESS MOISTURE - A MAJOR REASON WHY PRODUCING LANDSLIPS - Adelaida Cristina HONTUŞ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The soil is a porous medium with variable physical time and space that determine certain features of the mass of water flow. Sometimes these features prevent the formulation of mathematical laws describing these processes, requiring approximations of the physical process. For this reason, the approach to water movement through saturated soil to drain requires simplification actual physical processes and how they can be expressed by means of contemporary knowledge. This paper refers to a study on the factors and measures to combat a natural hazard. Natural hazards are several ways, and occur in different circumstances, but this paper will present the production conditions of landslides and methods / measures to combat them. It is known that excess moisture is one of the triggers of landslides. Also, to halt and prevent these natural disasters, various measures are necessary. Besides the determinants of a landslide, the study presents some of the measures against landslides, focusing on the drainage method. Water flow through saturated soil for drainage is a case of plane- parallel motion of fluid particles moving in transverse planes against the perpendicular axis of drainage.